School-based social and behavior change communication (SBCC) advances community exposure to malaria messages, acceptance, and preventive practices in Ethiopia: A pre-posttest study - Kebede, Yohannes (PLoS One, 2020)
BACKGROUND: Ethiopia has shown incredible success in malaria morbidity, mortality, and control. Community empowerment is a milestone to meet the ambitious plans of eliminating malaria by 2030. OBJECTIVES: This study aimed to evaluate school-based malaria social behavior change communication (SBCC) in terms of community message exposure, acceptance, knowledge, and practices. METHODS: A community-based pre-posttest study was conducted in five districts of the Jimma Zone, Ethiopia. 762 and 759 households were sampled for baseline and end-line, respectively. The intervention engaged students from primary schools on participatory peer education within small groups, followed by exposing parents with malaria messages aimed to influencing ideation and preventive practices. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 20.0. Proportion/mean differences were computed to compare both surveys on exposure, knowledge, perceptions, and practices at p <0.05. Finally, a regression analysis was conducted between key changes and school-based exposure. RESULTS: The study revealed a sharp increase in exposure to malaria messages with effect size (ES) of 65.7%, p <0.001. School specific exposure has grown to 57.8% (ES = 44.5%). Comprehensive knowledge about malaria increased to 39.1% (ES = 14.8%). Identifying mosquito bites as a cause of malaria was increased by ES = 20.8%. A slight reduction in risk perception (ES = 3.3%) and attitude (ES = 3.8%) and a higher rise in self-efficacy (ES = 8.5%) were observed. Community message acceptance in favor of malaria danger control was significantly improved by 10% i.e. an increase in rational decision making to uptake preventive practices. Consistently, insecticide-treated nets (ITNs) usage was improved to 63.0% (ES = 25.8%). Giving priority to use ITNs for under five years old children and pregnant women grew by 16.3% and 24.8%, respectively. Significant improvements were observed in treatment-seeking for fever (ES = 16.3%) and early treatment-seeking (ES = 15.5%). Not painting or plastering walls 6 months within spraying changed by ES = 61%. No significant change was observed in drug adherence. The school-based content intensity of exposure had effects on comprehensive knowledge, message acceptance, and ITN utilization. CONCLUSIONS: Engaging school-aged children effectively advances community exposure, perception, and behaviors. We recommend the inclusion of school-based SBCC in the national malaria control programs.